Comparing the efficiency of strengthening timber beams reinforced with carbon composite rods and plates - Bula, Serhiy; Pelekh, Andriy (Eastern-European Journal of Enterprise Technologies, 2023)
This study reports the results of experiments comparing the effect of structural reinforcement for timber beams strengthened with different carbon composite materials. Samples of one series were strengthened by gluing a carbon fiber plate from the outside to the face of the beam. The samples of the other series were strengthened by laterally gluing two carbon fiber rods inside the beam. According to the bending research program, the ultimate loads and deflections were determined for both series. As a result of the analysis of the results and comparison with unreinforced samples from the control series, the effect of beam reinforcement and the model of their destruction were determined. Studies have shown that the effect of external reinforcement with a plate was 86.7 % according to the criterion of full failure load, 20.5 % according to the criterion of ultimate load, 13.4 % according to the criterion of ultimate deflection. The effect of rod reinforcement was 48.6 %, 18.6 %, and 4.1 %, respectively. The theoretical analysis of the results showed a convergence of up to 8.2 % with the experimental results. External reinforcement with a plate compared to lateral gluing of rods showed better results due to the placement of the plate in the zone of maximum tensile stresses. This arrangement more effectively limited the spread of ultimate stresses and the development of cracks. The reinforcement parameters of the samples (materials, placement, percentage of reinforcement) were selected under the condition of the same theoretically predicted bearing capacity after reinforcement. However, comparative experimental studies have revealed differences in the processes of deformation and destruction of reinforced beams. The results will contribute to making rational project decisions and for choosing a relevant technique of strengthening timber beams with carbon composite materials